PRODUKSI MUSIK DIY (DO-IT-YOURSELF) SECARA DARING DENGAN INSPIRASI BUNYI LOKAL - Septian Okky Pradana; Azfar, Adimas Akma Danish; Bonggan Aditya; Favian Hassan Mulyatama; Muhammad Syafi'; Hartono; Restu Lanjari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Advances in digital technology have brought new developments in the practice of Do-It-Yourself (DIY) music production, enabling independent musicians to independently create, record, process, and distribute their work through online media. This paper examines DIY music production, utilizing local sounds as a source of creative inspiration, connecting modern technology with cultural identity. A variety of local sounds, such as traditional instruments, environmental sounds, and everyday atmospheres, are processed through sampling, field recording, audio editing, and sound design techniques to produce distinctive musical colors. DIY music production practices not only reflect artistic independence but also serve as a medium for cultural revitalization through the combination of traditional and electronic elements in hybrid compositions. On the other hand, the presence of digital platforms opens up broader opportunities for the distribution of works, online collaboration, and the strengthening of independent music community networks. However, this practice still faces various challenges, such as technical limitations, issues of cultural ethics, and the potential commodification of tradition. Therefore, a critical approach and respect for cultural values ​​are needed so that DIY music production based on local sounds can become a space for artistic innovation and an effort to preserve culture in the digital era.